Regulatory capital requirements and bank performance in Ghana: Evidence from panel corrected standard error - Joshua Nsanyan Sandow; Emmanuel Duodu; Eric Fosu Oteng-Abayie (Cogent Economics & Finance, 2021)
Over the past fifteen years, the Bank of Ghana has revised the minimum capital requirement to stabilize the banking sector. Motivated by the unintended consequences of regulatory capital, this paper provides empirical evidence between minimum capital requirement and bank performance relationship in Ghana. We draw data on a sample of 20 universal banks spanning 2008 to 2017. The Panel Corrected Standard Errors (PCSE) estimation was adopted. The results indicate that the minimum capital requirement has a significant positive impact on bank performance measured by return on assets (ROA) and equity (ROE). However, the effects turned negative after 1.7% and 1.6% performance thresholds for ROA and ROE, respectively. Given this, the study establishes the relationship between capital requirement and bank performance in Ghana to be double-edged. The capital requirement improves bank performance initially, but bank performance worsens after the threshold values. Policy implications for Ghana's banks, regulators, and policymakers have been provided based on the findings.
Keywords: C23; F38; G21; O55; 330; Bank performance; Ghana; Minimum capital requirements; PCSE